Influence of Employees’ Job Satisfaction and Performance on Health Care Delivery in Abia State University Teaching Hospital, Nigeria - Kanu, Chukwuka Edwin; Ihechu, Innocent Paschal (Global Journal of Social Sciences Studies, 2019)
Employee’s job satisfaction for high performance in the workplace has been of great concern since the beginning of industrial revolution. Satisfaction is believed to be fundamental to individual and organizational performance. To this end, in recent time, especially in a developing country like Nigeria, there has been increasing concern over the adverse implications of the failure to adequately satisfy all levels of employees in any work organization. It is on this context that this study looked at the employees job satisfaction and performance and its effect on health care provision, with reference to Abia State University Teaching Hospital Aba, Nigeria. The general objectives of this study is to examine the extent which employee job satisfaction and performance among health workers in Abia State University Teaching Hospital Aba, affect health care delivery in the institution. This study adopted a survey research design using structured questionnaire for qualitative data and in-depth interview for qualitative information. From the findings, it was concluded that despite the findings that majority of the workers were not satisfied in relation to the satisfaction indicators such as prompt payment of salaries, on the job training, objective promotion, payment of allowances, etc; the workers delivered their duties diligently. Finally, it was recommended that the hospital management should ensure regular and adequate staff training and development programmes with a view to improving staff skills, knowledge, attitude, ability, competence, and above all, satisfaction of the staff for optimum performance.